2021
DOI: 10.1029/2021jb021926
|View full text |Cite
|
Sign up to set email alerts
|

A New 1‐Hourly ERA5‐Based Atmosphere De‐Aliasing Product for GRACE, GRACE‐FO, and Future Gravity Missions

Abstract: The current state‐of‐the‐art of satellite gravity data processing makes use of de‐aliasing products to reduce high‐frequency mass anomalies. For example, the most recent official Atmosphere and Ocean De‐aliasing products (AOD1B‐RL06) are applied for the Gravity Recovery and Climate Experiment (GRACE) and GRACE‐Follow On (GRACE‐FO) missions. The temporal resolution of AOD1B‐RL06 is 3 h, and spectrally, they are computed up to degree and order 180. In this study, we explore a refined, e.g., geometrically, physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 52 publications
(121 reference statements)
0
25
0
Order By: Relevance
“…Recent improvements on the atmospheric part of the AOD product included (a) homogenizing surface pressure time-series from different NWP models to a common reference orography, (b) moving from ERA-I to ERA5, (c) moving from 6-hourly resolution to 3-hourly resolution or even 1-hourly resolution, and (d) updating geometric, physical, and numerical approximations. Forootan et al (2013) and Yang et al (2021) showed that a more realistic geometrical and physical shape of the Earth, together with better approximation of latitude-and altitude-dependent gravity acceleration in the vertical integration process, leads to differences in VIM of few 0.01 mm in terms of geoid height without degree 0 and 1 coefficients, that is, less than 1 mm EWH. With AOD-RL06 the temporal resolution of the de-aliasing product was increased from 6-hourly data to 3-hourly data, which lead to differences in the geoid of about 0.1 mm averaged over one year (Yang et al, 2021), that is, few mm EWH.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent improvements on the atmospheric part of the AOD product included (a) homogenizing surface pressure time-series from different NWP models to a common reference orography, (b) moving from ERA-I to ERA5, (c) moving from 6-hourly resolution to 3-hourly resolution or even 1-hourly resolution, and (d) updating geometric, physical, and numerical approximations. Forootan et al (2013) and Yang et al (2021) showed that a more realistic geometrical and physical shape of the Earth, together with better approximation of latitude-and altitude-dependent gravity acceleration in the vertical integration process, leads to differences in VIM of few 0.01 mm in terms of geoid height without degree 0 and 1 coefficients, that is, less than 1 mm EWH. With AOD-RL06 the temporal resolution of the de-aliasing product was increased from 6-hourly data to 3-hourly data, which lead to differences in the geoid of about 0.1 mm averaged over one year (Yang et al, 2021), that is, few mm EWH.…”
Section: Discussionmentioning
confidence: 99%
“…It should be kept in mind, that atmospheric tides were not removed here. However, their impact can be assumed to be not significant for our analysis in the mid-latitudes (Yang et al, 2021). Shihora et al (2022) found, after careful removal of tidal signals, contribution of hourly temporal resolution versus 3-hourly resolution of about 5 mm and decided based on that analysis to keep the official AOD product at 3-hourly resolution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations